Recensions (Judaïsme Ancien / Ancient Judaism, 2024)
Abstract Sonja Ammann – Katharina Pyschny – Julia Rhyder (ed.), Authorship and the Hebrew Bible, Tübingen, Mohr Siebeck, 2022, 277 pages (Forschungen zum Alten Testament, 158), compte rendu par David Hamidović Baptiste Sauvage, Le char des chérubins. Exégèse littérale d’Ézéchiel 1, préface de Philippe Lefevre, Paris, Cerf, 2023, 671 pages (Lectio divina, 284), compte rendu par Nabil Mili Sylvie Honigman–Christophe Nihan–Oded Lipschits (ed.), Times of Transition: Judea in the Early Hellenistic Period, University Park (Pennsylvanie) – Tel Aviv, Eisenbrauns – Tel Aviv University, 2021, 397 pages (Mosaics: Studies on Ancient Israel, 1), compte rendu par David Hamidović Anthony Giambrone, La Quête du Christ historique, traduction sous la diretion de RenaudSilly, préface de RégisBurnet, Paris, Les Belles Lettres, 2024, 523 pages, compte rendu par Pierluigi Piovanelli Yakir Paz, From Scribes to Scholars: Rabbinic Biblical Exegesis in Light of the Homeric Commentaries, Tübingen, Mohr Siebeck, 2022, xvi + 372 pages (Culture, Religion, and Politics in the Greco-Roman World, 6), compte rendu par Markham J. Geller